Xanthin Oxidase Activity of Acetone Extract from Cinnamomum burmannii (Nees & T. Nees) Blume. as an Antigout - Yoki Permana Agung; Sultan Rahwal; Suci Indah Ramadani; Friadi Ismed; Nurwahidatul Arifa (Universitas Labuhanbatu, 2025)
Background: Cinnamomum burmannii commonly referred to as Indonesian cinnamon, belongs to the Lauraceae family and is recognized for its substantial economic and pharmacological significance. The bark is predominantly utilized as it is enriched with bioactive constituents, including cinnamaldehyde, eugenol, and coumarin, which are known to exhibit antioxidant, antibacterial, antifungal, antidiabetic, and anti-inflammatory properties. In purine metabolism, xanthine oxidase (XO) functions as a key enzyme by facilitating the oxidation of hypoxanthine into xanthine and subsequently into uric acid. Elevated XO activity has been associated with increased uric acid levels, leading to conditions such as hyperuricemia and gout. Accordingly, this study was conducted to assess the inhibitory potential of the acetone extract of C. burmannii against xanthine oxidase activity. Methodology: Dried and authenticated bark samples were macerated using acetone as the extraction solvent. Xanthine oxidase inhibition was evaluated invitro using a UV–Vis spectrophotometric assay at 295 nm. Various extract concentrations (0.370–23.684 µg/mL) were tested under controlled conditions (pH 7.6, 25 °C, xanthine as the substrate). The IC₅₀ values were determined by linear regression analysis, and the relative inhibitory concentration (RIC₅₀) was calculated in comparison with allopurinol. Findings: The acetone extract of C. burmannii exhibited potent xanthine oxidase inhibitory activity with an IC₅₀ of 21.029 ppm (compared to allopurinol, IC₅₀ 2.7 ppm), demonstrating the potential of acetone as a solvent for extracting bioactive compounds, with a RIC₅₀ value of 0.13 indicating higher activity than previously reported ethanol extracts. Contribution: These findings indicate that acetone provides better selectivity in extracting compounds from C. burmannii, resulting in stronger xanthine oxidase inhibition. The acetone extract may serve as a promising natural alternative source for the development of antigout agents